On Going Losses After Hysterectomy Et Causa Uterine Atony (Journal of Pharmaceutical Negative Results, 2022)
Introduction: Postpartum hemorrhage (PPH) is an important cause of maternal mortality (MM) around the world. Seventy percent of thePPH corresponds to uterine atony.Background: Postpartum hemorrhages are obstetrical complications, which can rapidly become life threatening. They are defined as follows: ablood loss of either more than 500 ml after vaginal delivery or more than 750 ml after a Cesarean section. This type of hemorrhage is describedas severe when the blood loss consists of more than 1500 mL, more than 500 mL/min, or when hemoglobin concentration drops by at least4 g/dL. They can either be primary, when a blood loss of more than 500 mL occurs over the first 24 hours postdelivery, or secondary, whenexcessive bleeding occurs between the first 24 hours and 12 weeks post-delivery.Case A 28-year-old G1P1 postpartum with uncomplicated caesarian sectio, is readmitted to operating theatre four hours after delivery dueto increased vaginal bleeding. She reports that the bleeding began on the first hour after delivery and has increased in severity each subsequenthour. The obstetrics team has ruled out uterine atony as the cause of bleeding.Conclusion: Patients with severe hemorrhage and hypovolemic shock, the most important therapy is intravascular volume resuscitation, toreduce the possibility of target organ damage and death. The current proposals of transfusion therapy in massive hemorrhage point is earlytransfusion of blood products and use of fresh frozen plasma, in addition to packed red blood cells, to prevent maternal deaths.